PERHITUNGAN LAJU REAKSI NEUTRON DALAM REAKTOR SCWR (SUPERCRITICAL WATER REAKTOR) MODEL PERANGKAT (ASSEMBLY) HEKSAGONAL BERBAHAN BAKAR URANIUM - Sharen Herya Reafinola; Yanti Yulianti; Syafriadi Syafriadi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Calculation of the rate of fission and neutron capture reactions with a filter and without a filter has been carried out using a hexagonal geometry model using the REACT code SRAC program. This research uses uranium-235 and uranium-238 as fuel. Calculation results The rate of fission reaction in material 1 and material 3 using a filter and without a filter increases with the increase in the percentage value of U235 enrichment. The highest value for the neutron fission reaction rate of material 1 without a filter is found in the second mesh with 1% enrichment, which is 3.0747x10-2 reactions/cm3s. Meanwhile, the rate of neutron capture reaction using a filter increases with the increase in the percentage of U235 with 1% enrichment of the 5th mesh, with a value of 9.8627 x10-2 reactions/cm3s. Then the unfiltered neutron fission reaction rate on material 3 increased along with the increasing percentage in the 5th 1% enrichment mesh, which was 9.4778 x10-2 reactions/cm3s. This is due to the increasing percentage of U235 enrichment in the fuel pin. While the rate of capture reaction using a filter on material 1 with a percentage of 1% of the second mesh has the highest value compared to the filter, which is 9.8181 x10-2 reactions/cm3s.